PERENCANAAN KONFIGURASI KOMUNIKASI DARAT TERPADU - Amir, Ardi (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2011)
Switching process with the utilization of system LTR (Logic Trunked Radio) begins with the handshake between the mobile data with a repeater which ensures that the signaling does not occur on the wrong channel and prevents mobile with a strong signal using a channel that has been unused. Determination of the use of home repeater and channel ID in terms of flight safety and interests of users with uniformity throughout the airport which is determined by radio trunking operator. In terrestrial communication systems integrated with EF LTR. Johnson's lines of communication that is formed resembles the organizational structure chart so easily developed and communication links between the parts can be easily arranged. Â Keyword : radio trunked Logic, home repeater.